Łucjan Lange – a Teacher of Physical Education and Therapeutic Gymnastics Training, as well as a Pioneer of Physiotherapy - Maciej Łuczak; Aleksy Chmiel (Sport i Turystyka)
The purpose of this work is to show the formation process, his professional career, popularizing, teaching and organizational achievements in the field of physical culture and physical rehabilitation. Lucjan Lange was a respected physiotherapist, coach, athlete, academic teacher of Physical Education at the University of Poznań (he worked with Prof. Dr. Eugeniusz Piasecki, pioneer of the history of physical culture as a new scientific discipline, and Prof. Dr. Zdzislaw Grot, pioneer of the history of physical education in Poland), lecturer at the Medical Academy, the Higher School of Physical Education, the Agricultural Academy, the Medical Academy and Poznań high schools. He served as head of the Department of Therapeutic Physical Culture and as an instructor at the Department of Therapeutic Rehabilitation of the Orthopedic Medicine Clinic of the Poznan Medical Academy. He worked with the most prominent practitioners and theoreticians of Polish phys- iotherapy of the interwar period: Prof. Wiktor Dega, Prof. Kazimiera Milanowska and Doc. Janina Tomaszewska. He was among the forerunners of the application of new methods in therapeutic gymnastics; he organized and conducted staff training for rehabilitation departments. He served as secretary of the scientific journal “Physical Education” and was a member of district sports associations and clubs and national and international medical societies. While working at the University of Poznań’s Department of Physical Education, he taught classes in swimming, rowing, gymnastics, national dances, hand-to-hand combat, sports games, athletics and ice skating, among others. He presented methods for improving the compensation andadaptation of the musculoskeletal organ, muscle re-education and improvement after peripheral neuron damage. He has published dozens of popular science papers, the content of which he has presented at scientific conferences.